PRODUCTION AND CHARACTERIZATION OF IMMUNOGLOBULINE YOLK AS ANTI ANTIGEN MEMBRANE TOXOPLASMA GONDII - Puspitasari, Heni; Praptiwi, Yuliana; Suwanti, Lucia (Institute of Topical Disease Universitas Airlangga, 2016)
Toxoplasma gondii is an obligate parasite intracellular which can infected human and other mammalian. Immunoglobulin Y technology offers several advantages better than antibody production in mammals. This research was aimed to get immunoglobulin Y from egg yolk, to prove that antibody against membrane T. gondii antigen can produced from immunoglobulin Y and to know the characterization of immunoglobuline Y according to molecular weight by SDS PAGE and reactivation of antibody antigen by Western Blott. This research devided from many step : passase tachyzoites T. gondii into mice by peritoneal infection, cultivated the tachyzoite from intraperitoneal fluid, preparation of membrane antigen tachyzoite T. gondii, then immunization laying hens with membrane antigen, extraction and purification immunoglobuline Y from egg yolk and then protein analyzed by SDS PAGE and Western Blott. The result of this resarch showed that immunoglobulin Y from egg yolk can produced antibody against protein membrane T. gondii. The result of analyzed profile protein immunoglobuline Y according SDS PAGE has molecular weight 179,8 kDa. Analyzed from Western Blott showed that immunoglobulin Y can recognize antigen epitope of T. gondii on molecular weight 35,7 kDa and 78,8 kDa.